2020
DOI: 10.1186/s12917-020-02422-3
|View full text |Cite
|
Sign up to set email alerts
|

Study of the immunogenicity of the VP2 protein of canine parvovirus produced using an improved Baculovirus expression system

Abstract: Background: Canine parvovirus (CPV) is now recognized as a serious threat to the dog breeding industry worldwide. Currently used CPV vaccines all have their specific drawbacks, prompting a search for alternative safe and effective vaccination strategies such as subunit vaccine. VP2 protein is the major antigen targeted for developing CPV subunit vaccine, however, its production in baculovirus expression system remains challenging due to the insufficient yield. Therefore, our study aims to increase the VP2 prot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…PCR amplification of the VP2 gene has been used to detect wild FPV [21]. VP2 has been expressed in several hosts, including E. coli [22], insect cells [16,23,24], and a plant [25], for use as a subunit vaccine. We expressed VP2 in a baculovirus system, as revealed by IFA, WB, EM, and an HA test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR amplification of the VP2 gene has been used to detect wild FPV [21]. VP2 has been expressed in several hosts, including E. coli [22], insect cells [16,23,24], and a plant [25], for use as a subunit vaccine. We expressed VP2 in a baculovirus system, as revealed by IFA, WB, EM, and an HA test.…”
Section: Discussionmentioning
confidence: 99%
“…Baculovirus expression systems yield high levels of recombinant proteins and virus-like particles (VLPs) [15]. Several recombinant baculoviruses expressing VP2 of CPV and FPV have been created [16,17]. The recombinant VP2 proteins form VLPs via self-assembly and serve as antigens for subunit vaccines, enzyme-linked immunosorbent assays (ELISAs) [17,18], and HI tests.…”
Section: Expression Of the Vp2 Protein Of Feline Panleukopenia Virus mentioning
confidence: 99%
“…VLPs mimic virus particles and present considerable epitopes and are, therefore, capable of stimulating multiple immune responses [ 17 ]. Previous studies have shown that a variety of VLPs protein could be expressed in various expression systems, such as mammalian, insects, yeast, and E. coli [ 4 , 12 , 14 , 16 , 20 , 29] . To the best of our knowledge, there are no reports on the expression of RDPV VP2 till date.…”
Section: Discussionmentioning
confidence: 99%
“…The 4th ORF encodes VP2; this is the major capsid protein (constituting approximately 90% of the entire capsid). VP2 controls the host range and contains several important B cell epitopes that induce protective (neutralizing) antibodies during infection [6]. Of the 4 ORFs, the one encoding VP2 has been most commonly ex-…”
Section: Introductionmentioning
confidence: 99%